How You Pay Determines What You Get: Alternative Financing Options as a Determinant of Publicly Funded Health Care in Canada - Ronald D. Kneebone (The School of Public Policy Publications, 2012)
A Canadian returning home from a visit to a physician has no idea of the cost of providing the service just received. This is true for two reasons. One is because he or she does not receive a bill to pay. The other reason has to do the myriad of ways provincial governments fund the provision of health care. Health care is financed by a wide variety of types of taxation, by intergovernmental transfers determined by opaque and changing rules, by borrowing against future taxes and by drawing down savings. Confusion over how health care is funded creates a fiscal illusion that it is cheaper than it really is; a fiscal illusion that grows larger the less provincial governments rely on taxing individuals. In this paper it is shown that when provincial health spending is financed in ways other than taxation, it grows two to three times more quickly than it would have otherwise. From 2001-2008 alone, these distortions amounted to $6.75 billion at the national level, draining funds from other government services many of which have been shown to keep Canadians healthier and so reduce their demand for health care. Simply put, when Canadians are clear about the true cost of health care they more effectively play the traditional role of consumers by guarding against waste and inefficiency and so contribute to a more efficient and effective publicly-funded health care system.